Notes on Electoral and Parliamentary rights within the framework of the Revista de Ciencias Jurídicas - Matarrita Arroyo, Mario (2026)
This essay offers a thematic systematization of Electoral and Parliamentary rights within the framework of the commemoration of the 60th anniversary of the Revista de Ciencias Jurídicas, a publication that constitutes one of the main academic spaces for legal discussion in Costa Rica. Based on the contributions that appeared in that publication, the author refers to discussions that arose around, mainly, the exercise of the vote, political parties, the electoral process, the Costa Rican Supreme Election Tribunal, the judicialization of politics, the sanctioning procedures and the legislative function. Regarding these study phenomena, the authors of the articles in the Revista de Ciencias Jurídcas portray various aspects of a historical, political, cultural and legal nature - among others - of the Costa Rican legal system and, in some specific cases, of comparative law, all this in order to propose an in-depth look at its object of study.